Sistem Informasi Pelayanan Puskesmas Berbasis Web - Jenie Sundari - STMIK Nusa Mandiri (Universitas Bina Sarana Informatika, 2016)
ABSTRACT - Patient information systems in health centers is an information system that has a queue, registration and medical records of the patient. As for the performance of the system in patient care in health centers in generally not optimal because it is still in the processing of patient data and medical records are still using books or manuals. Therefore care patients at health centers become ineffective and inefficient, because bookkeeping making slow reporting. Method development of patient care systems in health centers is waterfall method with the design tools ERD ( Entity Relationship Diagram ) and LRS ( Logical Record Structure). Implementation of the program using the PHP language with using MySQL database. Patient care information system designed aiming to establish a computerized information system , making it easier for the health centers process patient data and patient medical records to be reported.ABSTRAKSI - Sistem informasi pasien pada puskesmas adalah sistem informasi yang mempunyai kegiatan antrian, registrasi, dan rekam medis pasien. Adapun kinerja sistem dalam pelayanan pasien yang berjalan pada puskesmas secara umum belum optimal karena masih pada pengolahan data pasien dan data rekam medis masih menggunakan media pembukuan atau manual. Maka pelayanan pasien pada puskesmas menjadi tidak efektif dan efisien, karena media pembukuan memperlambat pembuatan laporan. Metode pengembangan sistem pelayanan pasien pada puskesmas menggunakan metode waterfall dengan alat perancangan ERD (Entity Relationship Diagram) dan LRS (Logical Record Structure). Implementasi program menggunakan bahasa PHP dengan database menggunakan MySQL.Sistem informasi pelayanan pasien dirancang bertujuan untuk membangun sistem informasi yang terkomputerisasi, sehingga memudahkan pihak puskesmas mengolah data pasien dan rekam medis pasien hingga menjadi laporan.Kata Kunci : Sistem Informasi, E-Service, ERD, LRS, PHP.